Five children and it - Nesbit, E. (Edith), 1858-1924.; Avery, Gillian, 1926-2016.; Millar, H. R. (New York : Penguin Classics, 2005)
When four brothers and sisters discover a Psammead, or sand-fairy, in the gravel pit near the country house where they are staying, they have no way of knowing all the adventures its wish-granting will bring them.
Keywords: Fairies -- Fiction; Wishes -- Fiction; Brothers and sisters -- Fiction; Great Britain -- History -- Edward VII, 1901-1910 -- Fiction